2023
DOI: 10.3390/jof9020200
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Transcriptomic Analysis of Key Genes Involved in Citrinin Biosynthesis in Monascus purpureus

Abstract: Monascus pigments (MPs) display many beneficial biological activities and have been widely utilized as natural food-grade colorants in the food processing industry. The presence of the mycotoxin citrinin (CIT) seriously restricts the application of MPs, but the gene regulation mechanisms governing CIT biosynthesis remain unclear. We performed a RNA-Seq-based comparative transcriptomic analysis of representative high MPs-producing Monascus purpureus strains with extremely high vs. low CIT yields. In addition, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 42 publications
0
4
0
Order By: Relevance
“…Although mrl3, mrl4, mrl5, mrl6, mrl7, mrr1, and mrr5 were downregulated in the ihpRNA-pksCTα and ihpRNA-pksCT (α + β) transformants, the expression levels of mrl3, mrl5, mrr1, and mrr5 were lower in the latter transformant, potentially are closely associated with lower CIT yield. Huang et al [8] found that several genes involved in CIT biosynthesis were substantially downregulated in Monascus strains with low CIT yield (0.02 ± 0.01 mg/L). These genes included CtnG (encoding carbonic anhydrase; mrr5), CtnC (encoding membrane transporter/major facilitator superfamily protein; mrr1), CitB (encoding oxygenase; mrl2), CitD (encoding dehydrogenase; mrl4), CitE (encoding dehydrogenase; mrl6), and CitC (encoding oxidoreductase; mrl7).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Although mrl3, mrl4, mrl5, mrl6, mrl7, mrr1, and mrr5 were downregulated in the ihpRNA-pksCTα and ihpRNA-pksCT (α + β) transformants, the expression levels of mrl3, mrl5, mrr1, and mrr5 were lower in the latter transformant, potentially are closely associated with lower CIT yield. Huang et al [8] found that several genes involved in CIT biosynthesis were substantially downregulated in Monascus strains with low CIT yield (0.02 ± 0.01 mg/L). These genes included CtnG (encoding carbonic anhydrase; mrr5), CtnC (encoding membrane transporter/major facilitator superfamily protein; mrr1), CitB (encoding oxygenase; mrl2), CitD (encoding dehydrogenase; mrl4), CitE (encoding dehydrogenase; mrl6), and CitC (encoding oxidoreductase; mrl7).…”
Section: Discussionmentioning
confidence: 99%
“…However, DEGs related to the transformation of pyruvate to acetyl-coA were downregulated in both transformants. Regarding amino acid metabolism, most relevant DEGs were downregulated in the ihpRNA-pksCT (α + β) transformant, indicating reduced protein synthesis when CIT biosynthesis capacity was almost abolished [8]. Moreover, genes involved in the degradation of branched-chain amino acids (valine, leucine, and isoleucine) were upregulated.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For the initial growth, M. purpureus G11 was inoculated onto MEA slant (6% malt extract and 2% agar; pH 6-7; sterilized at 121 • C for 30 min) and incubated at 35 • C for 10 d. The seed and liquid media consisted of 6% glucose, 3% soluble starch, 1% peptone, 0.15% KH 2 PO 4 , 0.2% K 2 HPO 4 , 0.2% MgSO 4 , and 0.1% NaNO 3 without pH adjustment, and were sterilized at 121 • C for 30 min. The seed culture was prepared as described previously, and 6% of the seed was inoculated onto 50 mL of aseptic liquid fermentation medium and incubated at 35 • C and 180 rpm for 96 h [27].…”
Section: Strain and Culture Conditionsmentioning
confidence: 99%
“…MPs, oligoketides synthesized by the concerted action of polyketide synthase, fatty acid synthase and tailoring enzymes [ 6 , 7 ], can be divided into three groups according to their colour: yellow with absorption maxima in the light region at 330–450 nm, orange with absorption maxima in the visible light region at 460–480 nm and red with absorption maxima in the visible light region at 490–530 nm [ 6 ]. Figure 1 shows six major MPs, i.e.…”
Section: Introductionmentioning
confidence: 99%